ANALISIS RESEPSI GENERASI Z TERHADAP KONTEN BERBAGI PADA AKUN TIKTOK @IBEN_MA (Universitas Negeri Surabaya, 2023)
Generosity content is one of the content that is widely consumed by Indonesian people. This type of content raises pros and cons for the community because of differences in understanding of the kindness that is used as social media content. Iben's generosity content in the @iben_ma TikTok account has quite a different way of sharing. In his content, he gives some money to people around him who successfully complete the challenges that he gives. This research discusses how the generation Z group's message acceptance of generosity content on the TikTok account @iben_ma. In addition, how informants understand generosity is also discussed in this study. This research is a qualitative research that uses reception analysis method and interview as data collection techniques. The results of research that has been conducted on six informants resulted in one category of acceptance, that is negotiation. All informants agree that Iben’s generosity content is a kindness. Regarding generosity, all informants preferred not to show their generous activities. But on the other hand, the informants also provided notes on several aspects based on their understanding. For example, such as selecting people that need help, content packaging, and generosity content preferences. The similarity of acceptance of generation Z informants shows similar characteristics of thoughts and perspective towards an issue.